Construction Technique of Long-Span Shallow-Buried Tunnel Considering the Optimal Sequence of Pilot-Tunnel Excavation. (4th October 2015) - Jin, Bao; Liu, Yang; Yang, Changxi; Tan, Zhicheng; Zhang, Jianyang
Abstract : Construction technique considering the optimal sequence of pilot-tunnel excavation was investigated in order to ensure the safety of construction process of long-span shallow-buried tunnel. Firstly, optimal comparisons of the effect of different sequence of pilot-tunnel excavation on the ground settlement were implemented by the numerical analysis. Secondly, an optimal construction method was determined and applied to the construction of a practical tunnel. Some key issues and procedure of the selected construction method were described in detail. Finally, the numerical modeling and calculation of the tunnel construction process were conducted, and the effectiveness of these simulations was demonstrated by using the measured data of the practical tunnel.